Sistem Kontrol Stop Kontak pada Rumah Berbasis Arduino dan Android - Tanu Wijaya Saridin; Lily Puspa Dewi; Handry Khoswanto (Jurnal Infra, 2021)
The use of a smart home is one of the home control systems that provides comfort for homeowners to control electronic equipment using the internet. This concept is based on expanding the use and benefits of the internet of things by embedding a controller and sensor that can connect and share data continuously. Therefore, there is a smart home prototype that can control lights and electrical lines with easy access to control. This design, the device used is an Arduino Uno-based controller that is connected to a Wemos D1 Mini, Ac light dimmer, PZEM-004T sensor, PCB, and LCD. The method used is to log in to the android application and the system will respond to commands from the application and turn it into an aski, namely dimming and turning on the lights, or turning on and off electronic equipment. The final result of this journal is a tool that has been designed and an application that is used to make it easier for users to control electronic devices and check the electrical power used.